A ZIF-8@TPPa composite material, preparation method and application thereof, and adsorption method of herbicides in water
By preparing ZIF-8@TPPa composite material, the core-shell structure characteristics are used to solve the problems of low efficiency and difficulty in recycling of traditional adsorbent materials when removing water herbicides, and the efficient and environmentally friendly herbicide adsorption effect is achieved.
Patent Information
- Application Number
- CN202411095236.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-12
- Publication Date
- 2025-03-07
- Estimated Expiration
- 2044-08-12
AI Technical Summary
Traditional adsorbent materials are inefficient in removing herbicides in water bodies, are difficult to recover, are prone to secondary pollution, and are highly synthesised and poorly selective.
Using ZIF-8@TPPa composite material, this material is prepared by catalyzing Schiff base condensation reaction, combining the advantages of MOFs and COFs.
It has achieved efficient adsorption of herbicides, and has good chemical stability and recycling performance, reducing environmental pollution and production costs.
Smart Images

Figure CN118634800B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of adsorption materials, and in particular to a ZIF-8@TPPa composite material, a preparation method and application thereof, and a method for adsorbing herbicides in water. Background Art
[0002] Pesticides are chemical substances used to control crop pests. They can improve the quality of crops, ensure food production and supply, and occupy an important position in modern agricultural production. However, the increasing dependence on pesticides has led to an increase in the amount of pesticides used, and the pollution of natural environments such as soil and water bodies has also become increasingly serious. Among them, herbicide pollution in environmental water bodies is more serious. Compared with other water pollution treatment methods, adsorption has the advantages of wide applicability, good removal effect, simple operation, low cost, easy regeneration, environmental protection and pollution-free, and high degree of automation. After adsorption treatment, traditional adsorption materials (activated carbon, silica gel and molecular sieves, etc.) have low removal efficiency, difficult recovery, easy to cause secondary pollution, high synthesis cost and poor selectivity, and will affect the removal efficiency of pesticide residues in water. With the advancement of science and technology, new adsorption materials are becoming more and more important in the field of water pollution removal, including smart adsorption materials, chitosan, cellulose, metal organic framework materials (MOFs), covalent organic framework materials (COFs) and other materials are gradually replacing traditional adsorption materials.
[0003] Metal-organic frameworks and covalent organic frameworks, as two types of porous organic framework materials with development potential, have shown good advantages in various fields before. MOFs, which are constructed by metal ions and organic linkers through coordination bonds, have controllable functionality and adjustable structures. Their high porosity and high specific surface area have been widely studied. COFs, which have similar functions to MOFs, are synthesized through reversible covalent bonds of light elements. Their large surface area and high chemical stability have good potential in recyclable adsorption and separation. Although MOFs and COFs have many of the same characteristics (such as regular skeletons, high specific surface area, adjustable pore size, and strong adsorption capacity), they also show significant differences and complementarity. For example, although MOFs have unique properties, some types of MOFs are prone to bond breaking and structural collapse under acidic conditions, such as ZIF-8, which will cause the structure to be destroyed under acidic conditions. Although COFs have lower crystallinity and mass density, they generally have better chemical stability, so when MOFs or COFs are used alone, their performance has certain limitations. Summary of the invention
[0004] In view of this, the purpose of the present invention is to provide a ZIF-8@TPPa composite material and its preparation method and application, and a method for adsorbing herbicides in water. The ZIF-8@TPPa composite material prepared by the present invention has the advantages of both MOFs and COFs and has a good adsorption effect.
[0005] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:
[0006] The present invention provides a method for preparing a ZIF-8@TPPa composite material, comprising the following steps:
[0007] mixing p-phenylenediamine, ZIF-8, trialdehyde phloroglucinol, PbCl2 and an organic solvent to obtain a mixed solution;
[0008] The mixed solution is subjected to a catalytic Schiff base condensation reaction to obtain the ZIF-8@TPPa composite material.
[0009] Preferably, the mass ratio of ZIF-8 to trialdehyde phloroglucinol is 6:12-20.
[0010] Preferably, the mass ratio of ZIF-8 to p-phenylenediamine is 6:10-15.
[0011] Preferably, the temperature of the catalytic Schiff base condensation reaction is 120-150° C. and the time is 6-18 hours.
[0012] The present invention also provides a ZIF-8@TPPa composite material prepared by the preparation method described in the above technical scheme, which has a core-shell structure, with ZIF-8 as the core and COF-TPPa as the shell.
[0013] The present invention also provides the use of the ZIF-8@TPPa composite material described in the above technical solution in the adsorption of herbicides.
[0014] Preferably, the herbicide comprises one or more of butachlor, thiabendazim and pendimethalin.
[0015] The present invention also provides a method for adsorbing herbicides in water, comprising the following steps:
[0016] An adsorbent is added to the water body to be treated for adsorption, wherein the adsorbent is the ZIF-8@TPPa composite material described in the above technical solution, and the water body to be treated contains herbicides.
[0017] Preferably, the pH value of the water to be treated is 6.76-7.35.
[0018] Preferably, the mass ratio of the herbicide in the water to be treated to the ZIF-8@TPPa composite material is 0.1-20:5-100.
[0019] The invention provides a method for preparing a ZIF-8@TPPa composite material, comprising the following steps: mixing p-phenylenediamine, ZIF-8, trialdehyde phloroglucinol, PbCl2 and an organic solvent to obtain a mixed solution; and subjecting the mixed solution to a catalytic Schiff base condensation reaction to obtain the ZIF-8@TPPa composite material.
[0020] Compared with the prior art, the present invention has the following beneficial effects:
[0021] The present invention selects ZIF-8 in zeolite imidazole methyl ester framework (ZIFs) as the core of the material, obtains COF-TPPa (TPPa) by reacting trialdehyde pyrogallol and p-phenylenediamine, and designs and synthesizes ZIF-8@TPPa composite material on ZIF-8 by using COF-TPPa connected by imine bonds as the outer shell modification of the composite material. The composite material has the advantages of both MOFs and COFs and has good adsorption effect.
[0022] The present invention also provides a method for adsorbing herbicides in water. In the embodiment, liquid chromatography-tandem mass spectrometry (LC-MS / MS) is combined to analyze the efficient adsorption and removal effects of three herbicides (butachlor, thiamethoxam, and pendimethalin) in water. The optimal adsorption and removal conditions are obtained by exploring the dosage, adsorption time, pH value, etc. of the ZIF-8@TPPa composite material. At the same time, the recycling performance of the reuse of the ZIF-8@TPPa composite material is explored, and the method is applied to the adsorption and removal of herbicides in water bodies in different environments, which provides a new way to develop efficient and stable adsorption materials to treat herbicide residues in water bodies, so as to minimize the impact of pesticides on the environment and solve the challenges and limitations associated with the removal of pesticide residues. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] Figure 1 This is a flow chart of preparing ZIF-8@TPPa composite material according to an embodiment of the present invention;
[0024] Figure 2 (a) is the SEM image of ZIF-8, (b) is the TEM image of ZIF-8, (c) is the SEM image of COF-TPPa, (d) is the TEM image of COF-TPPa, (e) is the SEM image of ZIF-8@TPPa composite material, and (f) is the TEM image of ZIF-8@TPPa composite material;
[0025] Figure 3 XRD spectra of ZIF-8@TPPa, COF-TPPa and ZIF-8;
[0026] Figure 4Fourier transform infrared spectra of ZIF-8, TPPa and ZIF-8@TPPa;
[0027] Figure 5 (a) is the XPS full spectrum, (b) is the XPS fine spectrum of C1s, (c) is the XPS fine spectrum of O1s, and (d) is the XPS fine spectrum of N1s;
[0028] Figure 6 The effect of the dosage of ZIF-8@TPPa composite material on the adsorption rate of three herbicides;
[0029] Figure 7 The effect of different ionic strengths on the adsorption rate of herbicides;
[0030] Figure 8 is the adsorption rate of three herbicides in river water by ZIF-8@TPPa composite material;
[0031] Fig. 9 is the adsorption rate of three herbicides in seawater by ZIF-8@TPPa composite material;
[0032] Fig.10 is the adsorption rate of three herbicides in tap water by ZIF-8@TPPa composite material;
[0033] Fig.11 It is a bar chart of the recycling of ZIF-8@TPPa composites;
[0034] Fig.12 This is a bar chart comparing the adsorption performance of ZIF-8@TPPa, ZIF-8 and COF-TPPa for three drugs. DETAILED DESCRIPTION
[0035] The present invention provides a method for preparing a ZIF-8@TPPa (ZIF-8@COF-TPPa) composite material, comprising the following steps:
[0036] mixing p-phenylenediamine, ZIF-8, trialdehyde phloroglucinol, PbCl2 and an organic solvent to obtain a mixed solution;
[0037] The mixed solution is subjected to a catalytic Schiff base condensation reaction to obtain the ZIF-8@TPPa composite material.
[0038] In the present invention, unless otherwise specified, the raw materials used are all commercially available products in the art.
[0039] The present invention mixes p-phenylenediamine (Pa), ZIF-8, trialdehyde phloroglucinol (TP), PbCl2 and an organic solvent to obtain a mixed solution.
[0040] In the present invention, the mass ratio of ZIF-8 to trialdehyde phloroglucinol is 6:12-20, more preferably 6:17.4.
[0041] In the present invention, the mass ratio of ZIF-8 to p-phenylenediamine is preferably 6:10-15, more preferably 6:13.4.
[0042] In the present invention, the p-phenylenediamine and trialdehyde phloroglucinol are raw materials for synthesizing COF-TPPa (TPPa).
[0043] In the present invention, the PbCl2 is preferably used in the form of a saturated DMSO solution of lead chloride. The dosage ratio of the ZIF-8 to the saturated DMSO solution of lead chloride is preferably 6 mg: 30-80 μL, more preferably 6 mg: 50-60 μL. The PbCl2 is a catalyst that catalyzes the Schiff base condensation reaction. Since the ZIF-8 is not acid-resistant, lead chloride is used as a catalyst. The PbCl2 has a low acidity and does not destroy the structure of the reaction substrate material while playing a catalytic role.
[0044] In the present invention, the organic solvent is preferably methanol, dioxane or trimethylbenzene. The present invention has no special limitation on the amount of the organic solvent, as long as the raw materials can be mixed evenly.
[0045] In the present invention, the ZIF-8 is preferably prepared by a method comprising the following steps:
[0046] Weigh 1.625 g of 2-methylimidazole and place it in a beaker, then transfer 25 mL of methanol into the beaker to obtain a 2-methylimidazole solution; then dissolve 0.738 g of Zn(NO3)2·6H2O in 25 mL of methanol solution, and ultrasonically dissolve to obtain a zinc nitrate solution, which is then gradually added dropwise to the 2-methylimidazole solution. Finally, the product is centrifuged at 12000 rpm / min for 10 min, washed 3 times with methanol to remove unreacted monomers, and then dried in a vacuum drying oven at 60°C overnight to obtain white ZIF-8 crystals.
[0047] In the present invention, the p-phenylenediamine and ZIF-8 are preferably first added to a brown vial, and then methanol is added and ultrasonically dissolved, and then the trialdehyde phloroglucinol is added and ultrasonically dissolved for 10 minutes until the solution is uniformly dispersed, and then a saturated DMSO solution of lead chloride is added to the mixed solution and shaken for 10 seconds to obtain the mixed solution.
[0048] After obtaining the mixed solution, the present invention performs a catalytic Schiff base condensation reaction on the mixed solution to obtain the ZIF-8@TPPa composite material.
[0049] In the present invention, the temperature of the catalytic Schiff base condensation reaction is preferably 120° C., and the time is preferably 6 to 18 hours, more preferably 10 to 12 hours; during the catalytic Schiff base condensation reaction, COF-TPPa is first formed and then the ZIF-8 is wrapped.
[0050] In the present invention, the catalytic Schiff base condensation reaction is preferably carried out in a reactor.
[0051] After the catalytic Schiff base condensation reaction is completed, the present invention preferably cools the obtained hydrothermal product naturally to room temperature, repeatedly washes it with tetrahydrofuran (THF) and anhydrous ethanol, and then dries it to obtain the ZIF-8@TPPa composite material.
[0052] In the present invention, the drying is preferably vacuum drying, and the temperature of the vacuum drying is preferably 60° C. The present invention has no particular limitation on the time of the vacuum drying, as long as the solvent is completely removed.
[0053] The present invention also provides a ZIF-8@TPPa composite material prepared by the preparation method described in the above technical scheme, which has a core-shell structure, with ZIF-8 as the core and COF-TPPa as the shell.
[0054] The present invention also provides the use of the ZIF-8@TPPa composite material described in the above technical solution in the adsorption of herbicides.
[0055] In the present invention, the herbicide preferably includes one or more of butachlor, thiabendazim and pendimethalin.
[0056] The present invention also provides a method for adsorbing herbicides in water, comprising the following steps:
[0057] An adsorbent is added to the water body to be treated for adsorption, wherein the adsorbent is the ZIF-8@TPPa composite material described in the above technical solution, and the water body to be treated contains herbicides.
[0058] In the present invention, the pH value of the water to be treated is preferably 6.76-7.35.
[0059] In the present invention, the water body to be treated is preferably sea water, river water or tap water.
[0060] In the present invention, the mass ratio of the herbicide in the water to be treated to the ZIF-8@TPPa composite material is preferably 0.1-20:5-100, more preferably 0.2-4:20.
[0061] In the present invention, the adsorption temperature is preferably room temperature, that is, no additional heating or cooling is required.
[0062] The technical solutions in the present invention will be described clearly and completely below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only a part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0063] Figure 1 This is a flow chart of preparing ZIF-8@TPPa composite material according to an embodiment of the present invention.
[0064] Example 1
[0065] Preparation of ZIF-8@TPPa composites:
[0066] (1) Preparation of ZIF-8 crystals
[0067] Weigh 1.625g of 2-methylimidazole and place it in a beaker, then pipette 25mL of methanol into the beaker to obtain a 2-methylimidazole solution; then dissolve 0.738g of Zn(NO3)2·6H2O in 25mL of methanol solution, and dissolve it by ultrasonication to obtain a zinc nitrate solution. Then gradually add the zinc nitrate solution dropwise to the 2-methylimidazole solution. Finally, the product is centrifuged at 12000rpm for 10min, washed with methanol three times to remove unreacted monomers, and finally dried in a vacuum oven at 60°C overnight to obtain white ZIF-8 crystals.
[0068] (2) Preparation of ZIF-8@TPPa composites
[0069] Accurately weigh 13.4 mg of p-phenylenediamine and 6 mg of ZIF-8 and add them into a 30 mL brown vial, then add 25 mL of methanol and ultrasonically dissolve, then add 17.4 mg of trialdehyde pyrogallol and ultrasonically dissolve for 10 min until the solution is evenly dispersed, then add 50 μL of a saturated DMSO solution of lead chloride to the above mixture and shake vigorously for 10 s, then transfer the mixed solution to the lining of the reactor, react at 120 °C for 12 h, cool to room temperature, repeatedly wash the material with THF and anhydrous ethanol several times, and finally dry it in a vacuum drying oven at 60 °C to obtain a ZIF-8@TPPa composite material.
[0070] Concentration determination conditions of herbicides (butachlor, thiamethoxam, pendimethalin)
[0071] Liquid chromatography-tandem mass spectrometry (LC-MS / MS) was used to determine the concentrations of herbicides in the sample solutions before and after adsorption.
[0072] Liquid chromatography conditions: The chromatographic column was Luna Omega C18 column (100 mm×2.1 mm, 1.6 μm), and the column oven temperature was 35°C. The mobile phase was ammonium formate aqueous solution (5 mmol·L -1 , phase A) and methanol (phase B), using a gradient elution program, the gradient conditions are (volume fraction change): phase B is initially 5%, linearly increased to 40% within 0-1min, linearly increased to 80% within 1-3min, then increased from 80% to 95% within 3-5min, and maintained until 7min, and linearly decreased to 5% within 7-10min. The total running time is 10min, and the flow rate is 0.3mL·min -1 , the injection volume was 1 μL.
[0073] Mass spectrometry conditions: The tandem mass spectrometer was operated in multiple reaction monitoring (MRM) mode, using electron spray ionization (ESI), ESI capillary voltage was 4000 V, positive ionization mode, and ESI capillary temperature was 300 °C. The DL temperature was 250 °C, and the heating block temperature was 400 °C. Nitrogen was provided by a nitrogen generator, and argon was the collision gas. The flow rate was set as: heating gas (10 L min -1 , air), dry gas (10L·min -1 , nitrogen) and nebulizing gas (3 L min -1 , nitrogen).
[0074] The linear range of herbicides and pesticides in this determination method is 0.5~250µg / L. Based on the three-fold signal-to-noise ratio, the detection limit is 0.1µg / L. During the experiment, all samples were diluted to within the linear range before detection.
[0075] Experimental method for adsorption of pesticides
[0076] Use methanol solvent to prepare herbicide pesticide standards of 1000 mg·L -1 , and then the herbicide was prepared to 20 mg·L -1 20 mL of mixed standard aqueous solution was prepared. 20 mg of ZIF-8@TPPa composite material was weighed and placed in the herbicide aqueous solution. The mixture was shaken at 25 °C and 200 rpm for 30 min using a constant temperature shaker. The supernatant was aspirated and filtered through a 0.22 μm filter membrane. Finally, it was analyzed by LC-MS / MS. At the same time, the herbicide aqueous solution without ZIF-8@TPPa composite material was used as a control.
[0077] Verification of pesticide removal effect in actual samples
[0078] To verify the applicability of the method in removing herbicides in different environmental water bodies, seawater, river water, and tap water were collected. The pH value of the actual sample water samples ranged from 6.76 to 7.35, and herbicide mother solutions were added to the samples at concentrations of 0.005, 0.01, 0.2, and 1 mg·L -1 20 mL of aqueous solution was prepared, and 3 parallel samples were set for each concentration. 20 mg of ZIF-8@TPPa composite material was added to each centrifuge tube. The mixture was shaken in a constant temperature shaker at 25 °C and 200 rpm for 60 min. The supernatant was filtered with a 0.22 μm filter membrane and analyzed by LC-MS / MS.
[0079] Results and Discussion
[0080] Characterization of ZIF-8@TPPa composites
[0081] SEM and TEM were used to characterize the surface morphology. Figure 2 (a) is the SEM image of ZIF-8, (b) is the TEM image of ZIF-8, (c) is the SEM image of COF-TPPa, (d) is the TEM image of COF-TPPa, (e) is the SEM image of ZIF-8@TPPa composite material, and (f) is the TEM image of ZIF-8@TPPa composite material. From the SEM and TEM of ZIF-8, we can see that the prepared ZIF-8 has a regular morphology, a smooth surface, uniform size, and a regular dodecahedral structure. The SEM image of COF-TPPa shows a cluster rod structure, COF-TPPa shows a bouquet morphology, and the SEM image of ZIF-8@TPPa shows a neatly arranged cluster state. The TEM image of ZIF-8@TPPa is a core-shell structure, indicating that ZIF-8 and COF-TPPa have been successfully combined into a core-shell structure composite material. The crystal structures of ZIF-8@TPPa, COF-TPPa and ZIF-8 were studied by XRD. Figure 3 It can be seen that the characteristic peaks of ZIF-8 appear at 10.4°, 13.0°, 15.1° and 17.5°, and maintain a high degree of crystallinity, indicating that ZIF-8 has been successfully synthesized. COF-TPPa has characteristic peaks at 4.7° and 8.3°, and the characteristic peak at 26.7° may be due to the stacking of π-π bonds. The characteristic peaks of ZIF-8 and TPPa both appear in the XRD diagram of ZIF-8@TPPa, indicating that the ZIF-8@TPPa composite material has been successfully synthesized in the experiment.
[0082] Fourier transform infrared spectra of ZIF-8, TPPa and ZIF-8@TPPa are shown in Figure 4 As shown in the results, according to the analysis, the FT-IR of ZIF-8@TPPa shows 3300~3100cm -1The weak stretching vibration peak of the -NH bond at 1638 cm -1 The characteristic absorption peak corresponds to the vibration of the -C=O bond in TPPa. -1 and 1256cm -1 The characteristic absorption band at 421 cm belongs to the vibration of -C=C and -CN bonds of the imidazole ring of ZIF-8. -1 The absorption peak at comes from the vibration of Zn-N bond in ZIF-8. FT-IR proves that TPPa and ZIF-8 have been successfully combined.
[0083] X-ray photoelectron spectroscopy (XPS) was used to analyze TPPa, ZIF-8, and ZIF-8@COF-TPPa. Figure 5 (a) is the XPS full spectrum, (b) is the XPS fine spectrum of C1s, (c) is the XPS fine spectrum of O1s, and (d) is the XPS fine spectrum of N1s. The XPS full spectrum confirms that ZIF-8@COF-TPPa contains C, N, O and Zn elements. The four characteristic peaks with binding energies of 284.55 eV, 284.21 eV, 285.20 eV and 287.82 eV in the fine XPS spectrum of C1s correspond to C=C, C=N, C–C and C=O bonds, respectively. The O1s spectrum can be decomposed into three peaks at 530.64 eV, 532.12 eV and 533.30 eV, which belong to C-OH, O=C–C and O=CH bonds, respectively. The peak with a binding energy of 399.39 eV in the N1s fine spectrum is attributed to the CN bond, while the peak with a binding energy of 399.42 eV comes from the Zn-N bond. In addition, XPS full spectrum analysis showed that the binding energies of C1s, O1s, N1s, and Zn2p appeared in ZIF-8@COF-TPPa, which were consistent with the composition of ZIF-8 and TPPa, indicating that the ZIF-8@COF-TPPa composite material was successfully synthesized.
[0084] Effect of ZIF-8@TPPa dosage on herbicide adsorption rate
[0085] The effect of ZIF-8@TPPa composite material dosage on three herbicides (the concentration of herbicides in the test was 10 mg·L -1 , the volume of the herbicide solution is 20 mL) and the results are as follows Figure 6As shown, when the adsorbent dosage is 5 mg, the adsorption rate of butachlor is 74.6%, the adsorption rate of silyphos is 68.2%, and the adsorption rate of pendimethalin is 95.1%; within the dosage range of 5-20 mg, with the increase of the adsorbent dosage, the adsorption sites of the ZIF-8@TPPa composite material increase, and the adsorption rates of the three herbicides gradually increase. When the adsorbent dosage is 20 mg, the adsorption rate of butachlor is 90.4%, the adsorption rate of silyphos is 93.0%, and the adsorption rate of pendimethalin is 99.6%. When the dosage is 20-100 mg, the adsorption rate of butachlor is 80.3-85%, the adsorption rate of silyphos is 68.6-80.5%, and the adsorption rate of pendimethalin is 97.6-98.5%. Therefore, the present invention selects 20 mg of ZIF-8@TPPa composite material as the dosage condition for subsequent experiments.
[0086] Effect of ion interference on adsorption rate of herbicides
[0087] The effect of different ionic strengths on the adsorption rate of herbicides was evaluated. Figure 7 It can be seen that with the addition of NaCl, the adsorption of butachlor first increased, indicating that lower NaCl ion strength is conducive to its adsorption and removal. However, when NaCl continued to be added, the adsorption rate of butachlor began to decrease, which shows that excess NaCl will compete with butachlor for adsorbent sites and prevent it from diffusing in water; the adsorption rates of safflower and pendimethalin showed an upward trend with the increase of the relative mass of NaCl, and the relative mass of NaCl in the range of 0%~4% (referring to the mass concentration in aqueous solution) was conducive to the adsorption of safflower and pendimethalin; the adsorption rates of butachlor, safflower and pendimethalin increased with the increase of the relative mass of Na2SO4 and K2CO3. It can be seen that SO4 2- and CO3 2-The mass concentration range of ions in aqueous solution is 0%~4%, which is conducive to the adsorption of the three herbicides; in the mass concentration range of H3PO4 in aqueous solution is 0%~2%, the adsorption rates of butachlor and safflower gradually increase. When the mass concentration of H3PO4 in aqueous solution is 4%, the adsorption rates of the three herbicides begin to gradually decrease, and the adsorption rate of pendimethalin basically remains stable in H3PO4 ion solution; therefore, butachlor is in the range of 2% (referring to the mass concentration in aqueous solution) NaCl, 4% (referring to the mass concentration in aqueous solution) Na2SO4, The best adsorption effect was found in 4% (mass concentration in aqueous solution) K2CO3 and 2% (mass concentration in aqueous solution) H3PO4 solutions; the best adsorption effect was found in 4% (mass concentration in aqueous solution) NaCl, 4% (mass concentration in aqueous solution) Na2SO4, 4% (mass concentration in aqueous solution) K2CO3 and 2% (mass concentration in aqueous solution) H3PO4 solutions; the adsorption rate range of pendimethalin in the four ion solutions varied stably, and the adsorption rates all reached above 99.5%.
[0088] Actual sample verification
[0089] The adsorption and removal effect of ZIF-8@TPPa composite materials on herbicide residues in environmental water bodies (seawater, river water, tap water) was studied. Pesticide standard solutions were mixed in different actual environmental water bodies to make the pesticide concentrations in the aqueous solution 0.005, 0.01 and 0.5 mg·L -1 , the adsorption experiment was carried out according to the optimized adsorption conditions (20 mg of ZIF-8@TPPa composite material; shaking at 25 °C and 200 rpm for 30 min; the volume of the aqueous solution was 20 mL), such as Figure 8~Figure 10 As shown, the adsorption rate of ZIF-8@TPPa composite material for butachlor residues in river water, sea water and tap water can reach more than 85%, the adsorption rate of ZIF-8@TPPa composite material for safflower in river water, sea water and tap water can reach more than 88%, and the adsorption rate of pendimethalin can reach more than 96%. Overall, ZIF-8@TPPa composite material shows excellent adsorption performance and application prospects for the three herbicides in environmental water samples, which fully demonstrates the application potential of ZIF-8@TPPa composite material in actual water samples.
[0090] Cycle experiment
[0091] After five consecutive cycles of adsorption-desorption (desorption was eluted with methanol), the performance results of the adsorbent material were as follows: Fig.11As shown in the figure. The analysis data shows that the adsorption rate of butachlor is stable at about 80%; the adsorption rate of safflower is also maintained at more than 75%; in the adsorption and removal process of pendimethalin, the adsorption rate remains stable in five cycles, and the adsorption rate is higher than 97%; based on the above results, it can be concluded that the ZIF-8@TPPa composite material can still maintain a high adsorption rate even after multiple cycles, showing good cycle stability.
[0092] Comparison of the adsorption performance of three drugs among ZIF-8@TPPa, ZIF-8 and COF-TPPa
[0093] 10 mg of ZIF-8, COF-TPPa and ZIF-8@TPPa composite materials were weighed and placed in 10 mL of herbicide aqueous solution (0.2 mg / L). The mixture was shaken at 25 °C and 200 rpm for 30 min using a constant temperature shaker. The supernatant was aspirated and filtered through a 0.22 μm filter membrane. Finally, LC-MS / MS was used to analyze and calculate the herbicide concentration and removal rate adsorbed by each material. Fig.12 Among them, the removal rate of ZIF-8 for pendimethalin was 0, and the removal rate of TPPa for silyphos was 0. It can be seen that ZIF-8@TPPa exhibits higher adsorption and removal performance than ZIF-8 and COF-TPPa.
[0094] Example 2
[0095] Preparation of ZIF-8@TPPa composites:
[0096] (1) Preparation of ZIF-8 crystals
[0097] Weigh 1.625g of 2-methylimidazole and place it in a beaker, then pipette 25mL of methanol into the beaker to obtain a 2-methylimidazole solution; then dissolve 0.738g of Zn(NO3)2·6H2O in 25mL of methanol solution, and dissolve it by ultrasonication to obtain a zinc nitrate solution. Then gradually add the zinc nitrate solution dropwise to the 2-methylimidazole solution. Finally, the product is centrifuged at 12000rpm for 10min, washed with methanol three times to remove unreacted monomers, and finally dried in a vacuum oven at 60°C overnight to obtain white ZIF-8 crystals.
[0098] (2) Preparation of ZIF-8@TPPa composites
[0099] Accurately weigh 15 mg of p-phenylenediamine and 6 mg of ZIF-8 and add them into a 30 mL brown vial, then add 25 mL of methanol and ultrasonically dissolve, then add 17.4 mg of trialdehyde pyrogallol and ultrasonically dissolve for 10 min until the solution is evenly dispersed, then add 50 μL of a saturated DMSO solution of lead chloride to the above mixture and shake vigorously for 10 s, then transfer the mixed solution to the lining of the reactor, react at 120 °C for 12 h, cool to room temperature, repeatedly wash the material with THF and anhydrous ethanol several times, and finally dry it in a vacuum drying oven at 60 °C to obtain a ZIF-8@TPPa composite material.
[0100] The ZIF-8@TPPa composite material obtained in Example 2 was used to test the three herbicides (the concentration of the herbicides was 10 mg·L -1 The volume of the herbicide solution was 20 mL, and 20 mg of ZIF-8@TPPa composite material was used for adsorption test. The adsorption rates of butachlor, safflower, and pendimethalin were 90.3%, 92.0%, and 98.7%, respectively.
[0101] The above description is only a preferred embodiment of the present invention and does not limit the present invention in any form. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention, and these improvements and modifications should also be regarded as the protection scope of the present invention.
Claims
1. Application of ZIF-8@TPPa composite material in adsorption of herbicides, characterized in that: The herbicide comprises one or more of butachlor, thiabendazim and pendimethalin; The preparation method of the ZIF-8@TPPa composite material comprises the following steps: mixing p-phenylenediamine, ZIF-8, trialdehyde phloroglucinol, PbCl2 and an organic solvent to obtain a mixed solution; The mixed solution is subjected to a catalytic Schiff base condensation reaction to obtain the ZIF-8@TPPa composite material; The mass ratio of ZIF-8 to trialdehyde phloroglucinol is 6:12-20; The mass ratio of the ZIF-8 to p-phenylenediamine is 6:10-15.
2. The use according to claim 1, characterized in that: The temperature of the catalytic Schiff base condensation reaction is 120-150° C. and the time is 6-18 hours.
3. A method for adsorbing herbicides in water, characterized in that: The following steps are involved: Adding an adsorbent to the water body to be treated for adsorption, wherein the adsorbent is a ZIF-8@TPPa composite material, and the water body to be treated contains a herbicide; The herbicide comprises one or more of butachlor, thiabendazim and pendimethalin; The preparation method of the ZIF-8@TPPa composite material comprises the following steps: mixing p-phenylenediamine, ZIF-8, trialdehyde phloroglucinol, PbCl2 and an organic solvent to obtain a mixed solution; The mixed solution is subjected to a catalytic Schiff base condensation reaction to obtain the ZIF-8@TPPa composite material; The mass ratio of ZIF-8 to trialdehyde phloroglucinol is 6:12-20; The mass ratio of the ZIF-8 to p-phenylenediamine is 6:10-15.
4. The adsorption method according to claim 3, characterized in that: The pH value of the water body to be treated is 6.76-7.
35.
5. The adsorption method according to claim 3, characterized in that: The mass ratio of the herbicide in the water to be treated to the ZIF-8@TPPa composite material is 0.1-20:5-100.
Citation Information
Patent Citations
Yolk-eggshell MOF / COF composite material as well as template-free preparation method and catalytic application thereof
CN112642488A
Zeolite-like imidazate framework material as well as preparation method and application thereof
CN113717398A